1993
DOI: 10.1111/j.1432-1033.1993.tb17981.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and mutation of soybean β‐amylase in Escherichia coli

Abstract: The cDNA clones corresponding to soybean P-amylase mRNA were isolated and sequenced. The cDNA contained an open-reading frame composed of 496 amino acids. The comparison of the amino acid sequence deduced from the cDNA with the N-terminal peptide sequence from mature enzyme proved that P-amylase had no leader sequence. Employing the cDNA, the P-amylase was directly synthesized in Escherichia coli by the expression vector pKK233-2 controlled by the tac promoter. The enzyme activity detected in E. coli lysate dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…To identify the residues essential for catalytic activity of soybean P-amylase, we have tried to mutate cysteinyl, aspartyl, and glutamyl residues located in the highly conserved regions. Throughout these experiments, we have demonstrated that substitution of AsplOl and that of Glu186 of soybean P-amylase by neutral and acidic amino acids resulted in the complete elimination of the enzymic activity but did not alter the binding ability of a substrate analogue nor the circular dichroic spectra, as determined using an Escherichia coli expression system [4].…”
Section: -Amylase (1 4-a-d-glucan Maltohydrolase) Hydrolyzesmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify the residues essential for catalytic activity of soybean P-amylase, we have tried to mutate cysteinyl, aspartyl, and glutamyl residues located in the highly conserved regions. Throughout these experiments, we have demonstrated that substitution of AsplOl and that of Glu186 of soybean P-amylase by neutral and acidic amino acids resulted in the complete elimination of the enzymic activity but did not alter the binding ability of a substrate analogue nor the circular dichroic spectra, as determined using an Escherichia coli expression system [4].…”
Section: -Amylase (1 4-a-d-glucan Maltohydrolase) Hydrolyzesmentioning
confidence: 99%
“…As to aspartyl and glutamyl residues, AsplOl, Glu186, Glu345, and Asp348 of soybean P-amylase are contained in the above regions. Since mutation of Asp348 has already been shown not to affect the kinetic parameters [4], the targets for the mutation were focused on the AsplOl, Glu186, and Glu345 residues (Table 1). On the other hand, as to cysteinyl residues, the Cys95 in region I is highly conserved in every P-amylase known to date.…”
Section: Other Analytical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations